HAMBATAN BELAJAR SISWA DIKAJI DARI KEMAMPUAN LITERASI STATISTIK DI SEKOLAH MENENGAH PERTAMA - Mira Marlina; Sugiatno Sugiatno; Ahmad Yani T (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study is to explain the learning obstacles experienced by students in the ability of statistical literacy that students have in junior high school. The research method used is a descriptive method with the case study form of studies. The research agency is 5 students of Class IX G in SMP Negeri 2 Pontianak. The selection of the body is done by giving test literacy ability statistics and then 5 selected students each again given a test of difficulty and conducted interviews. The data collection techniques used are written tests and interviews. The data collection tools used are test instruments, hsse interviews, and cameras. The results of this research data analysis Products that in general the literacy skills of student statistics classified as Sell, from 36 students, obtained by the results of 8% students have a very high ability, 17% of students who are highly capable, 28% of students are capable, 33% Sell-enabled students and 14% of students are highly skilled. In addition, based on the results of the research, it is known that from 5 students, it is very easy to experience the didactic obstacles (didatical constraints), ontogenesis obstacles (ontogenic obstacles) and epsietemological obstacles (epistemological constraints).Keywords: statistical literacy, learning obstacles